2001
DOI: 10.1093/aje/153.7.659
|View full text |Cite
|
Sign up to set email alerts
|

Human and Pet-related Risk Factors for Household Evacuation Failure During a Natural Disaster

Abstract: This study characterized risk factors for household evacuation failure. A random digit dial telephone survey was conducted of 397 households in Yuba County, California, in July 1997, 6 months after residents had been under evacuation notice due to flooding. Case households failed to evacuate, whereas control households evacuated. The cumulative incidence of household evacuation failure was 19.4%. Fewer households with children (25.8%) failed to evacuate than households without children (45.9%, p < 0.01). More … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(95 citation statements)
references
References 15 publications
1
89
2
3
Order By: Relevance
“…A number of empirical studies support the view that households evacuate as a unit (e.g., Heath et al 2001;Sime 1993;Zelinsky and Kosinski 1991). Hence, it is implicitly assumed that evacuees belonging to a single household are either already all together upon evacuation or evacuate independently and meet up after arriving outside the threatened region.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of empirical studies support the view that households evacuate as a unit (e.g., Heath et al 2001;Sime 1993;Zelinsky and Kosinski 1991). Hence, it is implicitly assumed that evacuees belonging to a single household are either already all together upon evacuation or evacuate independently and meet up after arriving outside the threatened region.…”
Section: Discussionmentioning
confidence: 96%
“…In other words, these models describe the decisions of travellers regarding evacuation participation and departure time. These decisions are generally made at the household level (Dash and Gladwin 2007;Dow and Cutter 2000;Heath et al 2001;Whitehead et al 2000). We will in the following discussion however not consider at which level the decision is made, but how the resulting evacuation participation rates and departure time patterns are simulated.…”
Section: Travel Demand Modellingmentioning
confidence: 99%
“…For many people, the idea of leaving their companion animals behind during a disaster is unthinkable and there is a strong correlation, for example, between having companion animals and failure to evacuate in accordance with disaster warnings (Heath, Kass, Beck, & Glickman, 2001;Hunt, Bogue, &Rohrbaugh, 2012). The presence of companion animals during a disaster often leads to people staying in dangerous situations or attempting to evacuate with them, even if this places people and animals at increased risk (Hesterberg, Huertas, & Appleby, 2012).…”
Section: Companion Animals and Disasters: Lives At Riskmentioning
confidence: 99%
“…As a result of failures to plan in advance, ad hoc responses to meet the needs of animals have been a recurring feature in disasters (Heath & Linnabary, 2015) and there has been a tendency for individual HSOs to fail to incorporate, or to ignore, the human-animal bond in their planning and operations. There are a range of practical barriers that, in ignoring this bond, may prevent evacuation with companion animals, such as difficulty finding pet-friendly accommodation and inability to transport animals (Heath et al, 2001;Hunt et al, 2012).…”
Section: Animal-inclusive Planning In Organisationsmentioning
confidence: 99%
“…In a survey of North Carolina residents, for example, pet owners were approximately half as likely as non-pet owners to report evacuating during Hurricane Bonney and were even less likely to report willingness to evacuate in hypothetical future hurricane scenarios (Whitehead et al 2001). Similarly, a study of residents impacted by 1997 flooding in Yuba County, CA demonstrated that the likelihood of evacuation failure was associated with the number of household pets (Heath et al 2001). As another example of the impact of inadequate coordination, the high number of companion animals that were never reunited after Katrina has been attributed, at least in part, to the lack of coordination and planning by animal welfare organizations that transported animals away from the affected communities (Louisiana SPCA).…”
Section: Introductionmentioning
confidence: 99%